Commuting to Palmerston North : an examination of some aspects of the journey to work in the Palmerston North urban area : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Bang, Bryan Desmond (Massey University, 1970)
While this study could have been undertaken by another whose competence was in some other field, it is offered in the hope that the geographer's point of view may illuminate an area of knowledge about the Manawatu of which we were formerly ignorant. It is offered, too, in the hope of making a contribution, however meagre, to the literature which is available on the local area. At the outset of the study it was the intention to enumerate commuters in terms of origin areas, the sole destination considered being the Palmerston North Urban Area. The inflow of commuters to the major employment centre in the Manawatu was the main consideration but it was expected that commuting might shed some light upon the distribution of population in the district. It was felt that the existence of an urban hierarchy, formulated on the basis of population size and urban function might well be the result of forces operating both in the settlements and within the area as a whole. Changes within the hierarchy could then be viewed as resulting from alterations of the forces. It was considered that commuting, as it is currently operating, was having an effect upon the Manawatu hierarchy and that settlement patterns were possibly being stabilised or reinforced by the existence of commuting. In this way the examination of commuting as a phenomenon taking place within a changing hierarchy became an important aim and some attempt was made to equate changes in the hierarchy with commuting patterns.
Keywords: New Zealand Palmerston North; Commuting